Development of noodles prepared by partial supplementation with Taiwan Oolong banana and evaluation of their physicochemical characteristics - Shu Chen Hsu; Chin Fu Chou (Heliyon, 2024)
The physicochemical characteristics of noodles prepared using Taiwan Oolong banana were evaluated. To prepare noodles, wheat flour was partially substituted with Oolong banana flour (OBF) in different levels (0, 2.5, 0.5, 7.5 and 10 %). Noodles supplemented with OBF exhibited significantly higher cooking loss (5.50–6.29 %), hardness (0.80–1.18 kgf/mm2), and resistant starch content (RSC) (13.72–16.06 g/100g) compared to the control group (4.69 %, 0.43 kgf/mm2 and 11.47 g/100g for the cooking loss, hardness and resistant starch content). Regarding the color analysis results, the control group had a significantly higher L∗ value (black to white) than the noodles supplemented with OBF (p < 0.05), but the a∗ (red to green) and b∗ values (yellow to blue) (0.96, 3.61, 3.81, and 3.97 and 6.37, 12.47, 13.67, and 14.36; 0.70 and 5.15 for the control group) were contrary. Our results exhibited the formulated noodle products with Taiwan Oolong banana, thus offering greater quality for fine-tuning the properties of noodle products.